Ta’dib in a Multicultural Digital Society: A Conceptual Framework for Ethical and Inclusive Interactive Education - Hayati Ismail; Fauziah Hassan (Universitas Muhammadiyah Surakarta, 2026)
The rapid expansion of digital learning environments has intensified concerns regarding the erosion of ethical values, superficial engagement, and limited inclusivity in multicultural educational contexts. While contemporary educational policies emphasize digital competencies and future-ready skills, there remains a critical lack of integrative frameworks that align technological advancement with ethical and philosophical foundations. This study aims to develop a conceptual framework that integrates the Islamic educational philosophy of Ta’dib with interactive new media, in alignment with the Malaysia Education Blueprint 2026–2035, to foster ethical and inclusive learning. Employing a systematic integrative review design, this study synthesizes insights from three key domains: Islamic educational philosophy, digital pedagogy, and national education policy. Data were collected from scholarly literature and policy documents, and analyzed through thematic and comparative synthesis to identify conceptual convergences, gaps, and opportunities for integration. The findings propose a three-pillar conceptual framework that positions Ta’dib as the epistemological anchor, interactive new media as the pedagogical vehicle, and policy directives as the strategic context. The framework operationalizes ethical and holistic education through the Soft–Sharp–Smart competency structure and a recursive pedagogical cycle emphasizing intentionality, practice, reflection, and social impact. It demonstrates that digital technologies, when guided by ethical principles, can function as transformative environments for cultivating moral reasoning, intercultural competence, and responsible digital citizenship. The study contributes theoretically by bridging fragmented domains of philosophy, technology, and policy, and offers practical implications for educators and policymakers seeking to implement ethically grounded and inclusive digital education in multicultural societies.